2016
DOI: 10.1097/gox.0000000000001084
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Migraine Surgery Outcomes through Social Media

Abstract: Background:Social media have been used to study many aspects of health and human behavior. Although social media present a unique opportunity to obtain unsolicited patient-reported outcomes, its use has been limited in plastic and reconstructive surgical procedures, including migraine nerve surgery. The goal of this study was to utilize the most popular social media site, Facebook, to evaluate patients’ experience with migraine surgery.Methods:Six months of data regarding nerve surgery, nerve stimulators, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Social media platforms, such as Twitter and Facebook, have been steadily applied in medical education [ 33 , 34 ]. Facebook has been used to study many aspects of health care, and it provides a convenient and easily accessible way to collect unsolicited and observational patient data [ 35 ]. An analysis of the content of COPD group chats on Facebook showed that COPD Facebook group members share specific disease-related experiences and request information regarding select self-management topics.…”
Section: Discussionmentioning
confidence: 99%
“…Social media platforms, such as Twitter and Facebook, have been steadily applied in medical education [ 33 , 34 ]. Facebook has been used to study many aspects of health care, and it provides a convenient and easily accessible way to collect unsolicited and observational patient data [ 35 ]. An analysis of the content of COPD group chats on Facebook showed that COPD Facebook group members share specific disease-related experiences and request information regarding select self-management topics.…”
Section: Discussionmentioning
confidence: 99%
“…There are data to support the acceptance of invasive options based on use of frontal migraine decompression surgeries of both supratrochlear and supraorbital nerves by an endoscopic or trans palpebral approach by migraine patients 52–54 . Patients were willing to accept an invasive procedure for treatment of severe migraines based on medical information and other patient recommendations and advice by their peers about their experience with migraine surgery 55 . Therefore, we expect that an invasive procedure will be accepted among patient community through education when scientific data supporting the effectiveness of treatment will be available.…”
Section: Discussionmentioning
confidence: 99%
“…[52][53][54] Patients were willing to accept an invasive procedure for treatment of severe migraines based on medical information and other patient recommendations and advice by their peers about their experience with migraine surgery. 55 Therefore, we expect that an invasive procedure will be accepted among patient community through education when scientific data supporting the effectiveness of treatment will be available. We anticipate performing additional research in decision analysis in the health care context combining evidence and semiquantitative assessment of value placed by patients on desired outcomes and risk to determine the optimal strategy under given circumstances 56 to establish the "best" treatment from the patient perspective.…”
Section: Implications Of the Findingsmentioning
confidence: 99%
“…Patient-shared experiences in online health communities (i.e., social media and patient forums), as an easily accessible and efficient data source, have been widely used to assess treatment effects, adherence, and perceived quality of care from the end-user perspective [11][12][13][14][15][16][17][18][19]. Through these online health communities, patients have the opportunity to share their experiences, perceptions, feelings, and options with their peers.…”
Section: Introductionmentioning
confidence: 99%